SOME CONSIDERATIONS ON THE STUDY OF THE HISTORY OF MEDICINE AND TREATMENT METHODS - Abduraxmonova K. R (TARIXIY TADQIQOTLAR, 2025)
This article analyzes the historical stages of medicine, foreign studies, religious-mystical and scientific materialist theories. Also, healing traditions are analyzed based on material and written sources which are a unique component of folk culture, and information from ethnographic field research is given.